2020
DOI: 10.1590/s0102-865020200030000006
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of pharmacological blockade of the mitochondrial calcium uniporter on myocardial ischemia-reperfusion injury

Abstract: To evaluate whether the attenuation of mitochondrial Ca 2+ overload produced by pharmacological blockade of mitochondrial Ca 2+ uniporter (MCU) protects the myocardium against injuries caused by cardiac ischemia and reperfusion (CIR). Methods: CIR was induced in adult male Wistar rats (300-350 g) by occlusion of the left anterior descendent coronary artery (10 min), followed by reperfusion (120 min). Rats were treated with different doses of MCU blocker ruthenium red (RuR), administered 5 min before ischemia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 28 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…In this regard, using mCU transgenic mice, two independent groups confirmed our findings of the mCU’s critical role in matching the metabolic output during the adrenergic response ( Kwong et al, 2015 ; Wu et al, 2015 ). Blocking the mCU with ruthenium red (RuR) or Ru 360 min before the induction of ischemia-reperfusion (I/R) injury prevents the appearance of ventricular arrhythmia in rat models ( Garcia-Rivas Gde et al, 2006 ; Menezes-Rodrigues et al, 2020 ). In contrast, other studies have reported that enhancing Ca 2+ fluxes between the SR and mitochondria using mitochondrial Ca 2+ uptake enhancers is beneficial in preventing the appearance of ventricular arrhythmia associated with RyR2 dysfunction ( Schweitzer et al, 2017 ).…”
Section: Mitochondrial Ca 2+ Signaling and Cardiacmentioning
confidence: 99%
“…In this regard, using mCU transgenic mice, two independent groups confirmed our findings of the mCU’s critical role in matching the metabolic output during the adrenergic response ( Kwong et al, 2015 ; Wu et al, 2015 ). Blocking the mCU with ruthenium red (RuR) or Ru 360 min before the induction of ischemia-reperfusion (I/R) injury prevents the appearance of ventricular arrhythmia in rat models ( Garcia-Rivas Gde et al, 2006 ; Menezes-Rodrigues et al, 2020 ). In contrast, other studies have reported that enhancing Ca 2+ fluxes between the SR and mitochondria using mitochondrial Ca 2+ uptake enhancers is beneficial in preventing the appearance of ventricular arrhythmia associated with RyR2 dysfunction ( Schweitzer et al, 2017 ).…”
Section: Mitochondrial Ca 2+ Signaling and Cardiacmentioning
confidence: 99%
“…Surgical procedures used for induction of CIR in rats were made in accordance with methodology previously described [17][18][19] . Rats were anesthetized with urethane (1.25 g/kg), and fixed in the supine position.…”
Section: Surgical Procedures For Induction Of Cardiac Ischemia and Reperfusion (Cir)mentioning
confidence: 99%
“…After of 10 min of cardiac ischemia, the tourniquet was removed to allow coronary recirculation for 75 min (cardiac reperfusion). The cardiac electrical activity in all groups studied was monitored by electrocardiogram (ECG) system using a method previously described [17][18][19] . ECG analysis was performed during 100 min of duration (stabilization for 15 min, cardiac ischemia for 10 min and cardiac reperfusion for 75 min).…”
Section: Surgical Procedures For Induction Of Cardiac Ischemia and Reperfusion (Cir)mentioning
confidence: 99%
See 2 more Smart Citations